Peningkatan Hasil Belajar IPA Terpadu melalui Penerapan Model Pembelajaran Kooperatif Tipe NHT (Numbered Head Together) pada Siswa Kelas VIII-7 SMPN 1 Pringgasela - Azmi, Khairil (Lembaga Yasin AlSys, 2021)
This Classroom Action Research was conducted by applying the Cooperative Learning Model Type NHT (Numbered Head Together) in order to improve the quality of the learning process and is a concept of learning activities that assist teachers in carrying out Integrated Science learning activities that are taught by trying to maximize the active role of students, especially their knowledge. and how to apply it in everyday life. With this concept, learning outcomes are expected to be more meaningful for students. The learning process takes place naturally in the form of student activities working and experiencing, not transferring knowledge from teacher to student. The quality of learning is important. This Classroom Action Research (CAR) was conducted with the aim of knowing the improvement of Integrated Science learning outcomes through the application of the NHT (Numbered Head Together) type of cooperative learning model in class VIII.7 students in the 2020/2021 academic year. This Classroom Action Research (CAR) was carried out in stages 2 cycles, and from the results of the actions that have been carried out it has been proven to improve student learning outcomes both in terms of classical student learning completeness, namely in the first cycle by 70%, it can increase to 93% in the second cycle. This means that there is an increase of 23% and in terms of the average value of the evaluation results, namely in the first cycle of 71 to 77.5 in the second cycle, this means that there is an increase. From the results of this classroom action research, it also shows an increase in the level of student learning activity from the Moderately Active category in the first cycle to the Active category.